Similarities and differences in the categorization of disabilities and learning disorders in Europe - Vida, Gergő (Autonomy and Responsibility Journal of Educational Sciences, 2022)
Hungarian Law LXXIX of year 1993 about public education is, in many ways, considered to be up to date, however, it has defi ned the interpretability and compatibility of the Hungarian system for many years within the OECD, despite opening a new era, since the categories regarding to learning disorders described in the law mentioned above have been diffi cult to be adapted outside our homeland. Based on data from 2002, 2-2.5% of children in the European Union have been considered as disabled, however, the data from Hungary showed that this rate was 5,3% here, which is a signifi cant difference. The PISA surveys and the domestic experience have not verifi ed this hypothesis, so fi nding the factors affecting these results to such an instinct is reasonable. It is, however, even more important that the factors listed above have fundamentally determined the domestic evolution of special education approach, and, as a result, the professional protocol. This does not only lead to a different range of interpretation of the word ‘disabled’, but its fundamental effects can still be felt in the structure of the system. An example might be the procedure according to which a child, a student enters the special education care system. Determining or sequencing the diagnosis and provided care progresses in logic opposing that in particular OECD countries. We can conclude that not compatibility is the biggest issue, but the many questions, answering which is not necessarily the purpose, however, it might induce an interesting reasoning. The domestic system is not necessarily bad; however, the professional and causal backgrounds of the differences might need an explanation.